Water-permeable concrete brick loaded with metal-organic framework material and preparation method of water-permeable concrete brick
By loading metal-organic framework materials (MOF) in permeable concrete, the problem of insufficient adsorption efficiency of existing permeable concrete in water purification of heavy metal ions is solved, and the effect of significantly improving water purification performance and the ability to adsorb heavy metals is achieved.
Patent Information
- Application Number
- CN202411427083.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing permeable concrete has insufficient adsorption efficiency in water purification heavy metal ions, making it difficult to effectively remove heavy metal pollution in the environment.
By loading metal-organic framework materials (MOF) in permeable concrete, the high surface area and open structure of MOF are used to enhance the adsorption capacity of concrete. The specific method includes adding organic amine reagents to the mixture of silicon-aluminum materials and alkali activators to form a modified polymer slurry, then adding aggregates and metal salt solutions, and forming a permeable MOF-loaded membrane through steam curing and drying processes. Concrete bricks.
It significantly improves the water purification performance of permeable concrete, enhances the adsorption capacity of heavy metal ions, and can effectively remove heavy metal pollution in the environment in practical applications.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a permeable concrete brick loaded with a metal-organic framework material and a preparation method thereof. Background Art
[0002] With the rapid development of industries such as metal electroplating facilities, mining operations, fertilizer industry, tanneries, batteries, paper industry and pesticides, more and more heavy metal wastewater is discharged directly or indirectly into the environment, and wastewater contaminated by heavy metals entering the environment will have serious impacts on the ecosystem and human health.
[0003] Pervious concrete is made of interstitial graded coarse aggregate and cement paste, sometimes with the addition of chemical admixtures or supplementary cementitious materials. Since pervious concrete contains little or no fine aggregate, there are many open voids in its structure, allowing large amounts of water and air to pass through these interconnected macroscopic voids. Pervious concrete has a variety of environmental benefits, including controlling stormwater runoff, restoring groundwater supply, improving water quality, and reducing water and soil pollution. The two most basic components of pervious concrete are cement paste and aggregate, both of which have the ability to remove pollutants from the solution. The water purification capacity of pervious concrete is significantly affected by the adsorption capacity of its paste. This is because the strong alkaline conditions (pH>12) formed by cement hydration lead to metal precipitation or heavy metal ions adsorbed by cement hydration products (such as calcium-silicon dioxide-hydrate (CSH) gel). Therefore, pervious concrete has a certain water purification capacity, and the adsorption capacity of pervious concrete for heavy metals can be improved by modifying its paste, thereby improving the water purification effect.
[0004] Metal-organic frameworks (MOFs, also known as porous coordination polymers or PCPs) are an emerging class of porous materials composed of metal-containing nodes (also known as secondary building units or SBUs) and organic linkers, which are fixed in place by multidentate organic molecules through coordination bonds to form a cage-like structure. MOFs can be used in a variety of applications due to their high available surface area, adjustable pore size, open metal sites, and ordered crystal structure (which can be further tuned by changing the type and nature of metals and ligands and post-synthetic modifications). MOFs are widely used in the fields of energy storage, carbon fixation, liquid separation, purification, gas storage, photoluminescence, heterogeneous catalysis, drug delivery, sensing, and adsorption. In addition, MOFs can be synthesized on a large scale using low-cost and simple methods. In the past decade, various MOF materials have been reported for the adsorption and removal of heavy metal ions, including Pb 2+ 、Cd 2+ , Hg 2+ Cr 3+ Cr 6+ 、As 3+ and As 5+etc. The adjustable physical and chemical properties of MOF and the highly ordered porous structure make MOF a promising next-generation adsorption material for the effective removal of heavy metal ions. Currently, there are many studies on the use of MOF materials as adsorbents, and the technical research on the composite MOF materials is also gradually increasing. Studies have shown that loading MOF materials on other materials can help other materials achieve more efficient adsorption performance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a permeable concrete brick loaded with metal-organic framework material and a preparation method thereof in view of the deficiencies in the prior art. The permeable concrete brick provided by the present invention has good adsorption efficiency and can exert excellent water purification function in practical use.
[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0007] A method for preparing a permeable concrete brick loaded with a metal-organic framework material comprises the following steps:
[0008] A silicoaluminate material is mixed with an alkali activator to prepare a geopolymer slurry, an organic amine reagent is added to the geopolymer slurry, and the mixture is mixed and stirred to obtain a modified geopolymer slurry;
[0009] Add aggregate to the modified geopolymer slurry, mix well and then put it into a test mold, let it stand for 1-2 days and then demould to obtain a geopolymer permeable concrete brick, spray the metal salt solution evenly on the geopolymer permeable concrete brick, steam cure for 3-5 hours and then take it out;
[0010] The organic ligand solution is evenly sprayed on the cured geopolymer permeable concrete brick, and then steam cured for 18-22 hours. After the curing is completed, the brick is taken out and dried in an oven at 80-120° C. for 20-30 hours to obtain the permeable concrete brick loaded with the metal-organic framework material.
[0011] In the above scheme, the organic ligand solution is a mixture of an organic ligand and an organic solvent, wherein the molar ratio of the organic ligand to the organic solvent in the organic ligand solution is 1:(10-15); the organic ligand is one of trimesic acid, terephthalic acid, 2-methylimidazole, benzimidazole, and imidazole; and the organic solvent is one of methanol, ethanol, and dimethylamide.
[0012] In the above scheme, the metal salt solution includes a metal salt and the organic solvent, wherein the molar ratio of the metal salt to the organic solvent in the metal salt solution is 1:(8-17); wherein the metal salt is one of aluminum nitrate, aluminum chloride, cobalt nitrate hexahydrate, zinc nitrate, and zinc chloride.
[0013] In the above scheme, the molar ratio of the metal salt to the organic ligand is (0.25-5):1.
[0014] In the above scheme, the mass ratio of the silica-alumina material, the alkaline activator and the organic amine reagent is (3-3.2):(0.9-1):(0.2-0.4); the volume ratio of the permeable concrete brick slurry is 0.39-0.48, that is, the volume ratio of the modified polymer slurry to the aggregate is (0.39-0.48):1; the water-cement ratio of the permeable concrete brick is 0.43-0.46.
[0015] In the above scheme, the silicon-alumina material is one of fly ash, metakaolin, slag, coal gangue, steel slag or a mixture of any of them; the aggregate is crushed stone or pebbles for construction, wherein the particle size of the aggregate is 4.75-16 mm, with a single gradation.
[0016] In the above scheme, the alkaline activator is one of sodium hydroxide, sodium silicate, potassium hydroxide, potassium silicate or a mixed aqueous solution of any of them; the modulus M(SiO2) / n(Na2O) of the alkaline activator is 0.5-2, and the alkali equivalent is 5-20%.
[0017] In the above scheme, the organic amine reagent is one of ethylenediamine reagent and propylenediamine reagent; the purity of the organic amine reagent is 98wt%-99wt%.
[0018] In the above scheme, the conditions for steam curing are: relative humidity greater than 90% and temperature of 40-80°C.
[0019] The present invention also claims protection for the permeable concrete brick loaded with metal-organic framework material prepared by the method for preparing the permeable concrete brick loaded with metal-organic framework material.
[0020] In the present invention, there are more active functional groups in the geopolymer, but there is a lack of functional groups that are directly connected to MOF, and it is difficult to load MOF by direct use. The present invention first modifies the geopolymer slurry by an organic amine reagent to load the functional groups that can better connect to MOF, and then sprays the organic ligand and the metal salt solution separately during the steam curing process of the permeable concrete brick to generate the MOF structure during the steam curing process and connect with the permeable concrete brick. The improvement of the water purification function of MOF in permeable concrete is mainly related to the special structure of MOF itself. It is woven by metal ions and secondary structural blocks (organic ligands) through strong coordination bonds (network synthesis), thereby forming an open framework with high permanent porosity. When the MOF material is loaded on the cement slurry, thanks to the unique network structure of the MOF material, a large number of pores will appear in the cement slurry. The higher specific surface area and pores are conducive to the adsorption of heavy metal ions and other harmful substances by the cement slurry loaded with MOF material. There are a large number of active groups such as hydroxyl groups on the surface of geopolymers. Adding organic solvents can link functional groups that are more conducive to heavy metal binding to geopolymers, making the geopolymer-loaded MOF structure simple. On the other hand, modification with organic amine reagents can improve the mechanical properties of geopolymers. Reusing the steam curing process of concrete bricks, the MOF structure is loaded on permeable concrete by spraying metal salt solution and organic ligand solution. The two form a strong bond, and the cost of preparing raw materials is low and the manufacturing process is simple. Therefore, loading metal-organic framework materials (MOF) on permeable concrete can help improve the water purification performance of permeable concrete, greatly improve its ability to adsorb heavy metal ions and other harmful substances, and has a relatively broad application prospect.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The preparation method of a permeable concrete brick loaded with metal-organic framework material provided by the present invention combines MOF material with permeable concrete, utilizes the structural characteristics of MOF, enhances the adsorption of heavy metal ions by the slurry, improves the water purification performance of the permeable concrete, and is beneficial to environmental protection. At the same time, the structure of the geopolymer slurry plays a certain protective role on the MOF material, ensuring the adsorption of the MOF material.
[0023] (2) The preparation method of a permeable concrete brick loaded with a metal-organic framework material provided by the present invention is simple to operate, has a concise workflow, and has low raw material costs, and can be well applied in actual production. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0025] In a specific embodiment, the ethylenediamine reagent, cobalt nitrate hexahydrate, zinc chloride, and ethanol used are purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; 2-methylimidazole, benzimidazole, and imidazole are purchased from Wuhan Prov Biotechnology Co., Ltd.; water uses laboratory-made deionized water; sodium silicate is purchased from SP38 water glass produced by Jiashan Yourui Refractory Material Co., Ltd., whose modulus (i.e., the molar ratio of SiO2 and Na2O) is 3.3, the Na2SiO3 content is 35.5%, the Na2O content is 8.53%, and the SiO2 content is 26.98%; sodium hydroxide is a white granular solid particle purchased from Sinopharm Chemical Reagent Co., Ltd., and its content is ≥96%; the slag used in the experiment is S95-grade granulated blast furnace slag powder produced by a company in Wuhan.
[0026] Example 1
[0027] Take 47.70g NaOH, 95.69g SP38 water glass (Na2SiO3 content is 35.5%), and 133.03g water to prepare an alkaline activator, take 451.79g slag, add the alkaline activator thereto, mix well, then add 45.53g ethylenediamine reagent, and stir evenly to obtain a modified polymer slurry.
[0028] Add 1655 g of building crushed stone with a particle size of 9.5-13.2 mm to the mixed modified geopolymer slurry, place it in a stirring pot and stir it thoroughly for 1-2 minutes.
[0029] Pour the concrete into a cubic test mold of 100mm×100mm×100mm and remove it from the mold after leaving it to stand for 1 day.
[0030] Take 5.82g of cobalt nitrate hexahydrate and 10ml of ethanol to prepare a cobalt nitrate solution, spray it evenly on the six surfaces of the concrete brick, and send the concrete brick to the curing room for steam curing for 4 hours before taking it out.
[0031] 2.76g of 2-methylimidazole and 20ml of ethanol were mixed to prepare an organic ligand solution, which was evenly sprayed on the six surfaces of the permeable concrete brick, and then continued to steam cure for 20 hours. After being taken out, it was dried in an oven at 85°C for 24 hours to obtain a permeable concrete brick loaded with metal-organic framework materials. The steam curing conditions are: relative humidity greater than 90% and temperature of 60°C.
[0032] Example 2
[0033] Take 47.70g NaOH, 95.69g SP38 water glass (Na2SiO3 content is 35.5%), and 133.03g water to prepare an alkaline activator, take 451.79g slag, add the alkaline activator thereto, mix well, then add 45.53g ethylenediamine reagent, and stir evenly to obtain a modified polymer slurry.
[0034] Add 1655 g of building crushed stone with a particle size of 9.5-13.2 mm to the mixed modified geopolymer slurry, place it in a stirring pot and stir it thoroughly for 1-2 minutes.
[0035] Pour the concrete into a cubic test mold of 100mm×100mm×100mm and remove it from the mold after leaving it to stand for 1 day.
[0036] Take 1.96g of zinc chloride and 10ml of ethanol to prepare zinc chloride solution, spray it evenly on the six surfaces of the concrete brick, send the concrete brick to the curing room for steam curing for 4 hours and then take it out.
[0037] 2.29g of imidazole and 20ml of ethanol were mixed to prepare an organic ligand solution, which was evenly sprayed on the six surfaces of the permeable concrete brick, and then continued to steam cure for 20 hours. After being taken out, it was dried in an oven at 85°C for 24 hours to obtain a permeable concrete brick loaded with metal-organic framework materials. The steam curing conditions are: relative humidity greater than 90% and temperature of 60°C.
[0038] Example 3
[0039] Take 47.70g NaOH, 95.69g SP38 water glass (Na2SiO3 content is 35.5%), and 133.03g water to prepare an alkaline activator, take 451.79g slag, add the alkaline activator thereto, mix well, then add 45.53g ethylenediamine solution, and stir evenly to obtain a modified polymer slurry.
[0040] Add 1655 g of building crushed stone with a particle size of 9.5-13.2 mm to the mixed modified geopolymer slurry, place it in a stirring pot and stir it thoroughly for 1-2 minutes.
[0041] Pour the concrete into a cubic test mold of 100mm×100mm×100mm and remove it from the mold after leaving it to stand for 1 day.
[0042] Take 5.68g of cobalt nitrate hexahydrate and 10ml of ethanol to prepare a cobalt nitrate solution, spray it evenly on the six surfaces of the concrete brick, and send the concrete brick to the curing room for steam curing for 4 hours before taking it out.
[0043] 3.97g of benzimidazole was mixed with 20ml of ethanol to prepare an organic ligand solution, which was evenly sprayed on the six surfaces of the permeable concrete brick, and then continued to steam cure for 20 hours. After being taken out, it was dried in an oven at 85°C for 24 hours to obtain a permeable concrete brick loaded with metal-organic framework materials. The steam curing conditions are: relative humidity greater than 90% and temperature of 60°C.
[0044] Comparative Example 1
[0045] The permeable concrete bricks of this comparative example have the same steps as those of the above-mentioned Example 1, except that the ethylenediamine reagent is not mixed into the geopolymer and the metal salt solution and the organic ligand solution are not sprayed during the steam curing period, that is, ordinary geopolymer permeable concrete.
[0046] Comparative Example 2
[0047] The steps of the permeable concrete bricks in this comparative example are basically the same as those in the above-mentioned Example 1, except that the ethylenediamine reagent is not mixed into the geopolymer, that is, the metal salt solution and the organic ligand solution are sprayed to prepare the geopolymer permeable concrete without modification by ethylenediamine.
[0048] The permeable concrete brick samples prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to a water permeability test and a 28-day compressive strength test. The results are shown in Table 1, and all of them meet the permeable concrete performance requirements.
[0049] Table 1
[0050] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Water permeability coefficient (mm / s) 11.76 11.59 11.62 12.09 11.88 28d compressive strength (MPa) 14.95 14.64 14.83 15.20 15.10
[0051] The permeable concrete brick samples prepared in Examples 1-3 and Comparative Example were placed in Pb 2+ The static adsorption test of Pb(OH)2 with a concentration of 500 mg / L was carried out. 2+ Residual concentration to determine Pb 2+ The removal rate is used to judge the water purification effect. The experimental results of the embodiment and the comparative example are shown in Table 2:
[0052] Table 2
[0053] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 <![CDATA[Pb 2+ Removal rate]]> 96.5% 96.7% 97.1% 72.6% 78.3%
[0054] In summary, the permeable concrete brick loaded with metal-organic framework material provided by the present invention has good adsorption efficiency and can exert excellent water purification function in practical application.
[0055] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a permeable concrete brick loaded with a metal-organic framework material, characterized in that: The following steps are involved: A silicoaluminate material is mixed with an alkali activator to prepare a geopolymer slurry, an organic amine reagent is added to the geopolymer slurry, and the mixture is mixed and stirred to obtain a modified geopolymer slurry; Add aggregate to the modified geopolymer slurry, mix well and then put it into a test mold, let it stand for 1-2 days and then demould to obtain a geopolymer permeable concrete brick, spray the metal salt solution evenly on the geopolymer permeable concrete brick, steam cure for 3-5 hours and then take it out; The organic ligand solution is evenly sprayed on the cured geopolymer permeable concrete brick, and then steam cured for 18-22 hours. After the curing is completed, the brick is taken out and dried in an oven at 80-120° C. for 20-30 hours to obtain the permeable concrete brick loaded with the metal-organic framework material.
2. The method for preparing a permeable concrete brick loaded with a metal-organic framework material according to claim 1, characterized in that: The organic ligand solution is a mixture of an organic ligand and an organic solvent, wherein the molar ratio of the organic ligand to the organic solvent in the organic ligand solution is 1:(10-15); the organic ligand is one of trimesic acid, terephthalic acid, 2-methylimidazole, benzimidazole, and imidazole; and the organic solvent is one of methanol, ethanol, and dimethylamide.
3. The method for preparing a permeable concrete brick loaded with a metal-organic framework material according to claim 2, characterized in that: The metal salt solution comprises a metal salt and the organic solvent, wherein the molar ratio of the metal salt to the organic solvent in the metal salt solution is 1:(8-17); wherein the metal salt is one of aluminum nitrate, aluminum chloride, cobalt nitrate hexahydrate, zinc nitrate, and zinc chloride.
4. The method for preparing a permeable concrete brick loaded with a metal-organic framework material according to claim 3, characterized in that: The molar ratio of the metal salt to the organic ligand is (0.25-5):
1.
5. The method for preparing a permeable concrete brick loaded with a metal-organic framework material according to claim 1, characterized in that: The mass ratio of the silicon-aluminum material, the base activator and the organic amine reagent is (3-3.2): (0.9-1):(0.2-0.4); the permeable concrete brick mortar ratio is 0.39-0.48, and the water-cement ratio is 0.43-0.
46.
6. The method for preparing a permeable concrete brick loaded with a metal-organic framework material according to claim 1, characterized in that: The silicon-alumina material is one of fly ash, metakaolin, slag, coal gangue, steel slag or a mixture of any of them; the aggregate is crushed stone or pebbles for construction; wherein the particle size of the aggregate is 4.75-16 mm, with a single gradation.
7. The method for preparing a permeable concrete brick loaded with a metal-organic framework material according to claim 1, characterized in that: The alkaline activator is one of sodium hydroxide, sodium silicate, potassium hydroxide, potassium silicate or a mixed aqueous solution of any of them; the modulus M(SiO2) / n(Na2O) of the alkaline activator is 0.5-2, and the alkali equivalent is 5-20%.
8. The method for preparing a permeable concrete brick loaded with a metal-organic framework material according to claim 1, characterized in that: The organic amine reagent is one of ethylenediamine reagent and propylenediamine reagent; the purity of the organic amine reagent is 98wt%-99wt%.
9. The method for preparing a permeable concrete brick loaded with a metal-organic framework material according to claim 1, characterized in that: The steam curing conditions are: relative humidity greater than 90% and temperature between 40 and 80°C.
10. A permeable concrete brick loaded with a metal-organic framework material, prepared by the method for preparing a permeable concrete brick loaded with a metal-organic framework material as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Metal organic frameworks (MOFs)-amine modified / oxidized graphite composite material and preparation method thereof
CN103372420A
Porous alumina ceramic supporting Cu-MOF (Cu-metal organic framework) adsorbent and preparation method thereof
CN106268656A
Organic amino supported metallic organic framework-porous polymer composite material as well as preparation method and application thereof
CN108786755A
Preparation method for porous geopolymer gas adsorption material loaded with MOF
CN110694595A
Preparation method of three-dimensional MXene / MOF hydrogel and application of three-dimensional MXene / MOF hydrogel in water treatment
CN111151304A
Cited By
Cement-based composite material based on Ca-MOF in-situ growth and preparation method thereof
CN120097655A
Cement-based composite material based on in-situ growth of Ca-MOF and preparation method thereof
CN120097655B
Aluminum-based quick-setting inorganic multi-compound gelling agent and preparation method thereof
CN121159171A